Cohort study of cancer risk among male and female shift workers - Schwartzbaum, Judith; Ahlbom, Anders; Feychting, Maria (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'Melatonin, a hormone that inhibits experimentally induced cancers, is suppressed by nighttime exposure to light so that nighttime shift workers may be at an increased risk of cancer. Previous studies of shift workers found an increased risk of breast cancer among women and suggested a possible increased risk of colon cancer among women and prostate cancer. The present study was conducted to see whether these previous findings could be confirmed and whether shift workers are at elevated risk for cancer at additional sites. ' ' METHODS ': 'Altogether 2 102 126 male and 1 148 661 female workers were identified who worked in both 1960 and 1970. Their jobs were classified according to the percentage of shift workers, and they were followed from 1971 through 1989 or until they were diagnosed with cancer or died. Standardized incidence ratios (SIR) were used to compare the adjusted cancer incidence rates for shift workers with those for nonshift workers. ' ' RESULTS ': 'Cancer rates were not elevated for the male shift workers [all sites combined: N=6524 cases among shift workers, SIR 1.02, 95% confidence interval (95% CI) 1.00–1.05; prostate: N=1319, SIR 1.04, 95% CI 0.99–1.10] or for the female shift workers (all sites combined: N=268, SIR 1.00, 95% CI 0.89–1.13; breast: N=70 cases, SIR 0.94, 95% CI 0.74–1.18). ' ' CONCLUSIONS ': 'No evidence was found for an association between shift work and breast or prostate cancer, or all cancer sites combined among shift workers.
Keywords: cancer; cancer risk; cohort study; female; male; melatonin; shift worker